Penyuluhan Pengolahan Sampah Rumah Tangga (Pembuatan Kompos Dan Biopori) Dari Sisa Limbah Organik Dapur Bagi Tanaman Apotek Hidup Di Desa Baru Tahan - Iga Maliga; Herni Hasifah; Ana Lestari; Rafi'ah (Jurnal Pengabdian kepada Masyarakat Radisi, 2021)
This community based program aims to socialize household waste processing with composting and biopori methods. In addition, this training also provides residents with live pharmacy plants. This service was carried out in Baru Tahan Village, North Moyo District, Sumbawa Regency in December 2020. The purpose of this service is to increase public interest in treating their own household waste. In order to achieve the objectives, it consists of counseling and socialization with the stages of activities on planning, implementation, and evaluation. There were 20 participants, housewives, residents of Baru Tahan Village, North Moyo District. The percentage of participants' initial understanding on average is 65% in the less category. After the socialization, a questionnaire was filled out related to the interests and desires of the participants to apply the knowledge at the level of their respective homes. 85% of participants have an interest in implementing the knowledge gained. The results of the questionnaire are good responses, therefore this service activity is expected to be able to make people aware to process their household waste so as to produce products that can be recycled such as compost that can be of economic value. If the organic household waste left over from the kitchen cannot be composted, put it in the biopore hole so that it does not have an impact on the environment.